Patients and nurses opinions about the reasons for fear related to coronary angiography - Z Parsa-Yekta; Sh Basam Poor; A Mehran; H Esnaashari (Tehran University of Medical Sciences, 2003)
Fear is an undesirable feeling which most of the time results in physiological changes and can affect on the cardiovascular function of the patient. This research is a cross-sectional descriptive study that describes the congruency opinions between 91 patients /nurses about the reasons for patients' fear related to coronary angiography in two affiliated hospitals of Tehran University of Medical Sciences. The tools which were used included: questionnaire for study and recognition of patient and nurses demographic characteristics, a check list containing thirty probable reasons for patients' fear which were filled out by patients and nurses, and a scale for analysis of the reasons for fear which were filled out by patients, descriptive statistics indicators, sign test, and t-test were applied in order to analyze the data, by SPSS software. The results showed that patients' and nurses' ideas about the reasons for fear before angiography are similar in two cases and only in one case after the operation. Among the thirty probable reasons which were mentioned for patients' fear, seventeen cases caused less fear after angiography and two cases caused more fear after that. In the comparison between the intensity of fear caused by other reasons no insignificant result was observed. The comparison of intensity of fear showed that the intensity of patients' fear after angiography is less than before (p= 0.005). According to these cases it may be concluded that because of the different reasons for patients' fear concerning angiography, nurses need to pay more attention to patients' fear. It is also suggested that an assessment tool be used in order to assess issues relating to patients, level of care and training related to coronary angiography.